Live Streaming And The Spectacle Culture: A Critique of Modern Life Through The Lens of Maqāṣid Al-Syarī‘Ah - Abdillah Achmad Al Faruq; Qotadah, Hudzaifah Achmad Qotadah; Achmad, Adang Darmawan; Al Anshary, Abdurrahman Achmad (International Journal of Islamic Thought and Humanities, 2025)
This study critically investigates live streaming as a contemporary form of spectacle and examines its ethical, spiritual, and socio-cultural implications through the lens of Maqāṣid al-syarī‘ah. Live streaming has emerged as a pervasive phenomenon in the digital era, shaping interaction, consumption, and value formation patterns. While it provides unprecedented opportunities for self-expression, entertainment, and social connectivity, it also generates concerns about the commodification of attention, the superficiality of online engagement, and the erosion of deeper moral and spiritual orientations. Adopting a qualitative literature review design, this research synthesizes scholarly works from digital media studies, existential philosophy, and Islamic legal theory. The data set comprises peer-reviewed journal articles, books, and authoritative online sources published primarily within the last decade. Thematic content analysis was employed to identify recurring patterns related to the transformation of values in online interactions, particularly the shift from substance to image, and from intrinsic meaning to performative visibility. The findings reveal that excessive consumption of live streaming content contributes to ethical disorientation, weakens the internalization of moral values, and fosters an environment where identity is increasingly defined by curated appearances rather than authentic essence. Within this context, Maqāṣid al-syarī‘ah, articulated through its five higher objectives, ḥifẓ al-dīn (protection of religion), ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-nasl (protection of lineage), and ḥifẓ al-māl (protection of wealth), offers a comprehensive normative framework to assess and address these challenges. The study proposes ethically grounded and spiritually conscious approaches to digital engagement by integrating classical Islamic legal principles with contemporary media critique. This article contributes to contemporary Islamic scholarship by offering a conceptual framework to interpret the dominance of spectacle culture while proposing spiritually conscious and ethically grounded responses.